Effect of work boot shaft stiffness and sole flexibility on boot clearance and shank muscle activity when walking on simulated coal mining surfaces: implications for reducing trip risk. Issue 8 (3rd August 2022) - Dobson, Jessica A.; Riddiford-Harland, Diane L.; Bell, Alison F.; Wegener, Caleb; Steele, Julie R.
Abstract: Mining work boot shaft stiffness and sole flexibility variations are likely to affect how a miner moves their foot to clear the ground thus influencing their risk of tripping. Despite the potential negative consequences associated with tripping, limited research has investigated how these boot design features might contribute to a miner's trip risk. Therefore, this study aimed to investigate the effects of systematic variations to boot shaft stiffness and sole flexibility on lower limb alignment and shank muscle activity at toe off and boot clearance during initial swing when 20 males walked across two simulated coal mining surfaces. Although knee and hip alignment remained constant, changes to boot shaft stiffness and sole flexibility significantly interacted to influence the shank muscle activity and ankle alignment displayed at toe off. To reduce the risk of tripping, underground coal miners should avoid a boot with a stiff shaft, regardless of the sole flexibility. PRACTITIONER SUMMARY: Underground coal miners experience a high incidence of work-related lower limb injuries, with tripping a main cause. This study systematically investigated two boot design features that are likely to influence a miner's risk of tripping. To reduce trip risk, coal miners should avoid a boot with a stiff shaft.